2010
DOI: 10.1002/bip.21511
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographically observed folded topology of an unsubstituted γ‐aminobutyric acid incorporated in a model peptide: Importance of a CH···O interaction

Abstract: To validate the existing hypothesis put forward by Navarro et al., we performed single crystal X-ray diffraction structural analysis of a designed model peptide incorporating an unsubstituted achiral γ-aminobutyric acid: Boc-Pro-γ-Abu-OH (1) lacking C-terminal amide group. The analysis established existence of an overall unusual tightly folded topology stabilized by a conventional N(i)···H--N(i + 1) and an unconventional C(i)--H···O(i) type intramolecular hydrogen bonding interactions, encompassing a five-memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…[56][57][58][59][60] As shown in Figure 4, the observed FT-IR spectrum of the crystalline sample 1 in KBr disc displays intense absorption bands at $3435 and 3314 cm 21 in amide-A region and at $1745, 1676, and 1662 cm 21 in amide-I region. 33,58,59 The fact that molecular conformation of 1 is devoid of a conventional intramolecular hydrogen-bond, the appearance of two intense peaks in amide-A region may indicate the involvement of Thr O c H and amide-NH donor groups in strong intermolecular interactions. [56][57][58][59][60] The presence of a deep carbonyl absorption at $1745 cm 21 in amide-I region may be ascribed to the methyl ester participating in hydrogen-bonding interactions.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…[56][57][58][59][60] As shown in Figure 4, the observed FT-IR spectrum of the crystalline sample 1 in KBr disc displays intense absorption bands at $3435 and 3314 cm 21 in amide-A region and at $1745, 1676, and 1662 cm 21 in amide-I region. 33,58,59 The fact that molecular conformation of 1 is devoid of a conventional intramolecular hydrogen-bond, the appearance of two intense peaks in amide-A region may indicate the involvement of Thr O c H and amide-NH donor groups in strong intermolecular interactions. [56][57][58][59][60] The presence of a deep carbonyl absorption at $1745 cm 21 in amide-I region may be ascribed to the methyl ester participating in hydrogen-bonding interactions.…”
Section: Resultsmentioning
confidence: 96%
“…[45][46][47] In short peptides, the cis and trans peptide-bonds can exhibit marked influence on the overall preferred molecular structure and consequently, their shapespecific supramolecular self-assemblies. 33 Unexpectedly, the …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…j On the other hand, under these conditions, γ‐Abu exhibits strong bias for folded gauche ( θ 1 and/or θ 2 ∼±60±20°) dispositions 2. In fact, we recently demonstrated that even in the absence of a C‐terminal amide group, γ‐Abu, that is, the CONH(CH 2 ) 3 COOH moiety, adopted a folded conformation 2g. The existing literature inclined us to suggest that experimental characterisation of a fully‐extended γ‐Abu residue, that is, ϕ ≈ θ 1 ≈ θ 2 ≈ ψ ≈±180±20° conformation, could be rather demanding 2g.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, we recently demonstrated that even in the absence of a C‐terminal amide group, γ‐Abu, that is, the CONH(CH 2 ) 3 COOH moiety, adopted a folded conformation 2g. The existing literature inclined us to suggest that experimental characterisation of a fully‐extended γ‐Abu residue, that is, ϕ ≈ θ 1 ≈ θ 2 ≈ ψ ≈±180±20° conformation, could be rather demanding 2g. We believe that subtle modulation of folded structural features by inserting limited methylene units through β‐Ala and/or γ‐Abu residue(s) in appositely designed peptides could be constructive for expanding the range of accessible secondary structural components 1.…”
Section: Introductionmentioning
confidence: 99%